Child and adolescent development - Seifert, Kelvin; Hoffnung, Robert J. (Boston : Houghton Mifflin, 2000)
Incorporating a solid research base with real-life applications, Child and Adolescent Development illustrates the cognitive, psychosocial, and physical development of children in the context of today's society. The Fifth Edition includes increased coverage of the role of adults in the lives of children with expanded discussions of the applied and practical implications of developmental research for parenting, teaching, nursing, etc.
Includes bibliographical references and index.
Keywords: Child development; Adolescence